The application of DPE, CSEA, and EA in labor analgesia for nulliparous women and their impact on maternal and infant safety: DPE, CSEA, and EA in labor analgesia - Kang, Kai; Bai, Yunbo; Gong, Jie; Wang, Yue (Cellular and Molecular Biology, 2024)
This work compared the effects of dural puncture epidural (DPE), combined spinal epidural analgesia (CSEA) and epidural analgesia (EA) on labor analgesia for primiparae and their impacts on maternal and infant safety. A total of 204 primiparae in need of labor analgesia for vaginal delivery were allocated to DPE, CSEA and EA groups. At 10 min, 30 min and 1 h after analgesia, the DPE and CSEA groups showed lower VAS scores and quicker onset of action than EA group. There was no significant difference in the duration of analgesia and labor and fetal decelerations among the 3 groups. At 1 min and 5 min after childbirth, the neonatal Apgar scores showed no significant difference between the 3 groups. The Bromage scores of DPE and EA groups were lower than those of CSEA group. The incidence of pruritus, hypotension, and postpartum headache in DPE and EA groups were lower than those in CSEA group. To sum up, the efficacy of DPE in labor analgesia for primiparae is similar to that of CSEA, with no obvious effect on labor stage and neonatal Apgar score, no additional complications and less LLMB, pruritus, hypotension and postpartum headache.